(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In this new world today, Urban streets playing a major role as a heritage streets or commercialstreets and sometimes a residential or historical street. The concept of streets came from Roman periodand the use of streets as a surprising element can be seen in medieval period where end of the streetssurprisingly into a large space. The creation of vistas from a large square to one end of street gave aninteresting feel to visitor as seen in Renaissance period. Now the street policy is changed and ensure theright of way to be design and planned for all users with proper accessibility and safety. In India, thestreets planning and designing led by the transport engineers who gave always preferences to motorvehicles against the pedestrian walks. With 75 population will live in urban areas by 2050 and that timeurban streets need to balance the increasing vehicles and the city economy. When the city grows itgrows in all directions and it is important to consider the processes that shape our streets because theyare directly linked upon other urban systems and it is important to design them well for the benefit of thecities and its residents or visitors. Streets should not be seen in isolation or as transportation projectsalone, it should be evaluated on the basis of parameters likepedestrian safety, Urban realm, parking,loading activities. This paper talks about the concept of “Link and space design” by considering theusers safety on the street rather than vehicles in planning and design both. This paper helps tounderstand the desirable and minimum street performance indiceswith time and identifies the areas forimprovement and to determine the appropriate balance of street space and capacity. The aim of thispaper is to illustrate to redesign an urban high street to meet the needs of local residents, visitors andlocal businesses so that the street of that city play a major role as a social gathering space whichcontribute the quality of life in urban areas.